Digital Bas-Relief from 3D Scenes - Weyrich, Tim; et al. (Acm Transactions on Graphics, 2007)
We present a system for semi-automatic creation of bas-relief sculpture. As an artistic medium, relief spans the continuum between 2D drawing or painting and full 3D sculpture. Bas-relief (or low relief) presents the unique challenge of squeezing shapes into a nearly-flat surface while maintaining as much as possible the perception of the full 3D scene. Our solution to this problem adapts methods from the tone-mapping literature, which addresses the similar problem of squeezing a high dynamic range image into the (low) dynamic range available on typical display devices. However, the bas-relief medium imposes its own unique set of requirements, such as maintaining small, fixed-size depth discontinuities. Given a 3D model, camera, and a few parameters describing the relative attenuation of different frequencies in the shape, our system creates a relief that gives the illusion of the 3D shape from a given vantage point while conforming to a greatly compressed height.<br